Kinetic Study of Adsorption Active Carbon Cassava Skin for Removal of Acetic Acid from Aqueous Solution - Hartono, Tri; Murdiningsih, Hastami; HR, Yuliani (Politeknik Negeri Ujung Pandang, 2021)
The amount of liquid wastes containing acetic acid found from food industry such as tofu home industry released is relatively high and pollutes water quality and also environment nearby. Several methods reducing pollutant in liquid wastes are available, one of which is adsorption using carbon as an adsorbent. The production of cassava in Indonesia was about 23.936 tons in year 2013 which produced cassava’s skin wastes about 2.393 tons. Mostly these cassava’s skin wastes containing around 59.31% carbon is disposed as garbage. This research is to develop more on reducing acetic acid containing in liquid waste by carbon active from cassava’s skin with variation of particle sizes, reaction times and acetic acid liquid waste concentrations, and also to study the kinetic reaction of cassava skin active carbon adsorbing acetic acid between Freundlich and Langmuir isotherm equations. The result shows the kinetic adsorption follows Freundlich isotherm equation with maximum capacity of Cassava skin active carbon 0.7 mg/g at particle size of adsorbent of 0.3375 mm and reaction time of 105 minutes.